Symptoms of gonadal dysfunction are more predictive of hypopituitarism than nonspecific symptoms in screening for pituitary dysfunction following moderate or severe traumatic brain injury. (23rd September 2015) - Cuesta, Martín; Hannon, Mark J.; Crowley, Rachel K.; Behan, Lucy Ann; Tormey, William; Rawluk, Daniel; Delargy, Mark; Agha, Amar; Thompson, Christopher J.
Summary: Objective: The economic and logistic burden of screening for hypopituitarism following moderate/severe traumatic brain injury (TBI) is considerable. A key recommendation in published guidelines is to prioritize for screening those patients with symptoms suggestive of pituitary dysfunction. The purpose of this study was to evaluate the utility of targeted screening for hypopituitarism in long‐term survivors after moderate/severe TBI using referrals on the basis of symptoms. Design: In group 1 (G1), consecutive, unselected patients were screened from the Irish National Neurosurgery Centre, whereas in group 2 (G2) patients were targeted based on the presence of symptoms suggestive of pituitary dysfunction. Patients: A total of 137 patients (113 male) were systematically screened (G1) and compared to 112 patients (77 male) referred for pituitary evaluation on the basis of suggestive symptoms (G2). Main outcome measures: The rate of GH, ACTH, gonadotrophin (GT), TSH and ADH deficiency was compared among groups. Results: Patients referred with menstrual dysfunction had more GH (50% vs 11%, P = 0·001), ACTH (60% vs 14%, P < 0·0001), GT (90% vs 16%, P < 0·0001) deficiency and any pituitary hormone deficit (80% vs 33%, P = 0·003) than G1. Men with symptoms of hypogonadism had more GH (33% vs 11%, P = 0·003), GT (58% vs 16%, P < 0·0001) and TSH (16% vs 1%, P = 0·03) deficiency than G1. Patients with nonspecific symptoms were no more likely to have hypopituitarism than those consecutively screened. Conclusions: Symptoms of hypogonadism are sufficiently predictive of hypopituitarism to justify screening for hypopituitarism after moderate/severe TBI. Nonspecific symptoms of hypopituitarism are no more predictive than unselected screening.